Fatigue in Older Adults Postmyocardial Infarction - Crane, Patricia Barton; Efird, Jimmy T.; Abel, Willie Mae (Frontiers in Public Health, 2016)
Objective. The purpose of this study was to comprehensively examine putative factors that may independently contribute to fatigue and subsequent persistence of fatigue in elderly adults 6-8 months post myocardial infarction (MI). Studies suggest cardiac function, comorbidities, daytime sleepiness, depression, anemia, interleukins, and social support are correlates of fatigue; however, no studies have systematically examined these factors 6 months post MI in an aging population. Methods. Study participants included 49 women and men (N=98) ages 65 to 91 who were 6-8 months post MI. Data collection included the Demographic Health Status Questionnaire (heart rate, blood pressure, body mass index, medications), Fatigue-Related Comorbidity Scale, Revised Piper Fatigue Scale, Epworth Sleepiness Scale, Geriatric Depression Scale, Social Provisions Scale and venous blood tests (b-natriuretic peptide, hemoglobin, interleukin-6). Results. Fatigue persisted after MI in 76% of older men and women with no difference by sex. Only depression scores (Ptrend=.0004) and mean arterial pressure (Ptrend=.015) were found to be linearly independent predictors for fatigue, controlling for age, Il-6 levels, and body mass index. Conclusions. Post MI depression and mean arterial blood pressure are important to assess when examining fatigue post MI in older populations.